28/15x1/16x3+(8/15-69/60x5/23):-51/54
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a.\)
\(\dfrac{17}{8}:\left(\dfrac{27}{8}+\dfrac{11}{2}\right)\)
\(=\dfrac{17}{8}:\left(\dfrac{27+44}{8}\right)=\dfrac{17}{8}:\dfrac{71}{8}=\dfrac{17}{8}\cdot\dfrac{8}{71}=\dfrac{17}{71}\)
\(b.\)
\(\dfrac{28}{15}\cdot\dfrac{1}{4^2}\cdot3+\left(\dfrac{8}{15}-\dfrac{69}{60}\cdot\dfrac{5}{23}\right):\dfrac{51}{54}\)
\(=\dfrac{28}{15}\cdot\dfrac{1}{4^2}\cdot3+\left(\dfrac{8}{15}-\dfrac{1}{4}\right):\dfrac{51}{54}\)
\(=\dfrac{28}{15}\cdot\dfrac{1}{4^2}\cdot3+\left(\dfrac{8\cdot4-15}{60}\right):\dfrac{51}{54}\)
\(=\dfrac{28}{15}\cdot\dfrac{1}{4^2}\cdot3+\dfrac{17}{60}:\dfrac{51}{54}\)
\(=\dfrac{28}{15}\cdot\dfrac{1}{16}\cdot3+\dfrac{17}{60}\cdot\dfrac{54}{51}\)
\(=\dfrac{7}{20}+\dfrac{3}{10}\)
\(=\dfrac{7+3\cdot2}{20}=\dfrac{13}{20}\)
\(-8.4+19=-32+19=-13\)
\(-11.3-28=-33-28=-61\)
\(4.\left(-15\right)-18=-60-18=-78\)
\(19-4.\left(-12\right)=19+48=67\)
\(-25.\left(-3\right)-54=75-54=21\)
\(-16-7.\left(-4\right)+24\div\left(-8\right)=-16+28-3=9\)
\(15\div\left(-3\right)+30-7.\left(-3\right)=-5+30+21=46\)
\(-48\div\left(-4\right)+15.\left(-5\right)=12-75=-63\)
\(-29+65\div\left(-5\right)+23=-29-13+23=-19\)
\(15\div\left(-5\right)-17-12.\left(-5\right)=-3-17+60=40\)
\(28.\left(-4\right)-17=-112-17=-129\)
\(-19-7.4=-19-28=-47\)
\(-14.\left(-2\right)-16=28-16=12\)
\(13.\left(-3\right)-65-4.\left(-6\right)=-39-65+24=-80\)
\(-24-8.\left(-6\right)+28=-24+48+28=52\)
Chúc bạn hok tốt!!! tỷ tỷ
(15x1-15) x) (10+1+2+3+4+5+6+7+8+9+10+11+12+13+14+15+16+17+18+19+20)
= (15-15) x (10+1+2+3+4+5+6+7+8+9+10+11+12+13+14+15+16+17+18+19+20)
= 0 x (10+1+2+3+4+5+6+7+8+9+10+11+12+13+14+15+16+17+18+19+20)
= 0
= (15 - 15)\(\times\)(10 +1 +2 +3 +4 +5 +6 +7 +8 +9 +10 +11 +12 +13 +14 +15 +16 +17 +18 +19 +20)
= 0\(\times\)(10 +1 +2 +3 +4 +5 +6 +7 +8 +9 +10 +11 +12 +13 +14 +15 +16 +17 +18 +19 +20)
= 0
=\(\dfrac{28.3}{15.16}+\left(\dfrac{8}{15}-\dfrac{69.5}{60.23}\right).\dfrac{-54}{51}\)
=\(\dfrac{7}{20}+\left(\dfrac{8}{15}-\dfrac{1}{6}\right).\dfrac{-54}{51}\)
=\(\dfrac{7}{20}+\left(\dfrac{16}{30}-\dfrac{5}{30}\right).\dfrac{-54}{51}\)
=\(\dfrac{7}{20}+\dfrac{11}{30}.\dfrac{-54}{51}\)
=\(\dfrac{7}{20}+\dfrac{-99}{255}\)
=\(\dfrac{357}{1020}+\dfrac{-396}{1020}\)
=\(\dfrac{-39}{1020}\)